Estrategias administrativas de afrontamiento para mitigar el síndrome de burnout en el personal médico del Hospital IESS Latacunga. - Alex Rodrigo, Erazo Nogales (2018)
Occupational stress which workers are frequently exposed trigger multiple affectation on them, like is Burnout Syndrome, pathology also known as condition of being burned at work., it alters to several workers’ groups, among them it is headed by medical staff and it characterizes mainly by emotional exhaustion, depersonalization and loss of interest about incoming who has it. The purpose of this research is measuring the prevalence itself at IESS LATACUNGA HOSPITAL staff, for which a population of 155 people were taken among specialist, residents, general doctors and nursing staff who are medical ones and they represent the 100% of the sample that meet with inclusion criteria, for which the Maslach scale was applied that measure three levels that make up the syndrome. After analyzing the initial situation, six Bournout cases were determined which corresponding to 3,87 percent from the total population studied, and in the same way, high levels determined in the personal exhaustion and depersonalization dimension and moderate in the loss interest about personal fulfillment, in the whole studied population. After that the number of cases and the grade of syndrome involvement in different dimensions were determined, a guide was established to prevent new cases and face those already existing, this guide has standards and administrative policies and playful activities in order to improve the labor conditions for them. It is applied in a period of five months in the Institution and the second measure will be doing with the Maslach scale showing the reduction of number of cases to four from total population, of the intensity of the three components that comprise the syndrome, as well as the effects that develop from it such as absenteeism and morbidity in the institution staff.